The Effectiveness of SAVI Learning in Achieving Communication Ability and Mathematical Disposition for Eighth Grader - Fauziah, Fauziah; WINARTI, ENDANG RETNO; Kartono, Kartono (Department of Mathematics, Universitas Negeri Semarang, 2017)
Penelitian ini bertujuan untuk menganalisis keefektifan pembelajaran SAVI pada pencapaian kemampuan komunikasi dan disposisi matematis siswa kelas VIII materi persamaan garis lurus. Populasi dalam penelitian ini adalah siswa kelas VIII SMP Negeri 1 Kaliwungu Tahun Pelajaran 2015/2016 sebanyak 268 siswa. Sampel diambil secara acak sebanyak 68 siswa yang terdiri dari kelompok eksperimen yang memperoleh pembelajaran SAVI dan kelompok kontrol yang memperoleh pembelajaran direct instruction. Metode pengumpulan data yang digunakan adalah observasi, tes, dan angket. Analisis tes kemampuan komunikasi matematis menggunakan uji t dan uji proporsi. Simpulan dari penelitian ini adalah pembelajaran SAVI efektif pada pencapaian kemampuan komunikasi dan disposisi matematis siswa kelas VIII materi persamaan garis lurus. This research aimed to analyze the effectiveness of SAVI learning in achievement of mathematical communication’s ability and mathematical disposition of students on VIII grade in line equation. The Population in this research is class VIII SMP Negeri 1 Kaliwungu in the school year of 2015/2016 as many as 268 students. The samples were selected randomly as many as 68 students which consist of two group that is the an experimental group which applied SAVI learning and a control group which applied direct instruction. Methods of data collection were used observation, test, and questionaire. Analysis of mathematical communication’s ability test using the t test and proportions. Conclusions from this research that SAVI learning is effective in achievement of mathematical communication’s ability and mathematical disposition of students on VIII grade in line equation.